Bioreactors for low-pH iron(ii) oxidation remove considerable amounts of total iron. Issue 57 (20th July 2017) - Sheng, Yizhi; Kaley, Bradley; Bibby, Kyle; Grettenberger, Christen; Macalady, Jennifer L.; Wang, Guangcai; Burgos, William D.
Abstract : Rates of Fe(ii ) oxidation in chemostatic bioreactors can be predicted based only on the influent Fe(ii ) concentration and pH value. Abstract : Low-pH Fe(ii ) oxidation occurs naturally in certain acid mine drainage (AMD) systems and can be incorporated into passive treatments by enhancing the development of terraced iron formations (TIFs). For extremely difficult-to-treat AMD (very low pH, high concentrations of Fe(ii ) and associated metals), an active treatment bioreactor may be required. Based on field studies of eight low-pH TIF sites in the Appalachian Bituminous Coal Basin, US, two sites that displayed the fastest and regional-average rates of Fe(ii ) oxidation were selected to enrich for Fe(ii )-oxidizing microbes in chemostatic bioreactors with controlled geochemistry. After 74 to 128 days of fed-batch enrichment periods and a series of hydraulic residence time (HRT) experiments, four bioreactors (two for each site) were operated in flow-through mode through a series of pH set-points (pH 2.1 to 4.2; fixed [Fe(ii )]in ) or influent Fe(ii ) concentrations (80 to 2400 mg L −1 ; fixed pH) for an additional 52 to 138 days using site-specific anoxic AMD as influent. Fe(ii ) oxidation kinetics in bioreactors were remarkably similar from two sites that displayed significantly different field rates. Fe(ii ) oxidation rates were faster at high flow rate, low pH and high Fe(ii ) concentrations, consistent with field results. A three-parameter dual-Monod rate law was developed to describe Fe(ii ) oxidation kinetics solely based on pH and Fe(ii ) concentration, and agreed well with some other bioreactor and field studies. Importantly, these bioreactors also effectively removed total Fe at rates 7 to 20 times better than passive treatment settling ponds and TIFs sites, at optimal pH between 2.9 to 3.3. All of these results point to the promise of bioreactors enriched by natural-occurring acidophilic Fe(ii )-oxidizing microbes for AMD treatment.